Fault Current Level Analysis of Future Microgrids with High Penetration Level of Power Electronic-Based Generation - Khan, Hussain Sarwar; Fuad, Khaled Syfullah; Karimi, Mazaher; Kauhaniemi, Kimmo (IEEE, 2021)
The integration of power electronics-based generation has increased in the medium voltage (MV) level of the distribution networks, nowadays. It is obvious that the contribution level of this type of source is providing a limited fault current level according to the thermal and fault ride-through capability of power electronic converters. Therefore, the fault current level in the grid-connected and islanded mode of the microgrid is different and the protection scheme is required to be reviewed. In this regard, converters’ responses contribute to the stability of the microgrid in the case of abnormal conditions. This paper has investigated the effect of power electronic converters and their controllers in future microgrids with the high penetration level of power electronic-based generation. A distribution management system has been designed to address the issues and challenges of faulty conditions and a voltage ride-through technique has been proposed. The simulation results of an MV distribution network demonstrate the fault current level of the future microgrid in abnormal conditions. The proper protection strategy is designed to detect any type of short circuit fault current as well as avoidance of damage to the integrated PEC-based generations.
Keywords: Distribution management system; fault level detection; fault current; microgrid; power electronic converter-based generation; voltage ride-through; renewable energy sources; microgrids; fi=Sähkötekniikka|en=Electrical Engineering|